Achieving Remote Stress and Temperature Dual‐Modal Imaging by Double‐Lanthanide‐Activated Mechanoluminescent Materials. (9th April 2021) - Chen, Changjian; Zhuang, Yixi; Li, Xinya; Lin, Feiyan; Peng, Dengfeng; Tu, Dong; Xie, An; Xie, Rong‐Jun
Abstract: Mechanoluminescence (ML) is one of the most important routes to realize remote sensing of stress distribution, but has never been used in temperature sensing. Traditionally, stress sensing and temperature sensing are separately realized through different methods in multifunctional sensors, which definitely makes the structure more complicated. In this work, the remote stress–temperature dual‐modal sensing is proposed by using the double‐lanthanide‐activated ML material SrZnSO:Tb, Eu, where the stress is read by the integral intensity of ML and the temperature is displayed by the green to red emission ratio ( I Tb / I Eu ) of ML in one material. The dual sensing mode in SrZnSO:Tb, Eu enables building of a new imaging system, providing a facile, reliable, and more sensitive way to remotely visualize the distribution of stress and temperature. It opens up a novel approach to develop advanced artificial skins with simplified structures in human–machine interfaces, structural health monitoring, and biomedical engineering applications. Abstract : Remote stress and temperature dual‐modal imaging is achieved by using double‐lanthanide‐activated mechanoluminescent (ML) materials. The magnitude of stress is given by the integral intensity of ML, and simultaneously the temperature is determined by the ratio of ML intensity. This multifunctional material has potential in intelligent artificial skin, structural health monitoring, and biomedical engineering applications.